Anti-Inflammatory Potential and Synergic Activities of Eclipta prostrata (L.) L. Leaf-Derived Ointment Formulation in Combination with the Non-Steroidal Anti-Inflammatory Drug Diclofenac in Suppressing Atopic Dermatitis (AD) - Muhammad M. Poyil; Mohammed H. Karrar Alsharif; Mahmoud H. El-Bidawy; Salman Bin Dayel; Mohammed Sarosh Khan; Zainab Mohammed M. Omar; Alaaeldin Ahmed Mohamed; Reda M. Fayyad; Tarig Gasim Mohamed Alarabi; Hesham A. Khairy; Nasraddin Othman Bahakim; Mohamed A. Samhan; et al. (Life)
Atopic dermatitis (AD) or eczema is an important inflammatory chronic skin disease that brings many complications in its management and treatment. Although several chemical agents are used for treatment, the search for better anti-inflammatory and antibacterial agents of plant origin has been ongoing, since natural compounds, it is commonly believed, are less dangerous than synthetic ones. Therefore, the present study explored a medicinal plant—Eclipta prostrata (L.) L.—for its anti-inflammatory activity alone and in combination with a non-steroidal anti-inflammatory drug (NSAID), diclofenac. The plant extract was used to make a cream formulation for treating atopic dermatitis and as an antibacterial agent against Staphylococcus aures, the major infectious agent associated with AD. The phytochemical analysis of the E. prostrata extract showed the presence of various phytochemicals, including flavonoids, Tannin, saponin, terpenoids, glycosides, phenol, alkaloids, quinone, and protein. The GC-MS profiling of methanolic E. prostrata extract was performed predicted the presence of twenty important phytochemicals, including 2-[5-(2-Hydroxypropyl) oxolan-2-yl]propanoic acid, dl-Menthol, dodecane, undecane, 4,7-dimethyl-, dodecane, 2,6,10-trimethyl-, decane, 2,3,5,8-tetramethyl-, cholest-5-en-3-ol, (3.alpha.)-, TMS derivative, cyclopropane carboxylic acid, 1-hydroxy-, (2,6-di-t-butyl-4-methylphenyl) ester, alpha.-farnesene, propanoic acid, 2-methyl-, 2-ethyl-1-propyl-1,3-propanediyl ester, diethyl phthalate, corticosterone, 2-methylpropionate, hentriacontan-13-ol, O-TMS, phthalic acid, 2,4-dimethylpent-3-yl dodecyl ester, hexasiloxane, 1,1,3,3,5,5,7,7,9,9,11,11-dodecamethyl-, acetic acid, 4-t-butyl-4-hydroxy-1,5-dimethyl-hex-2-ynyl ester, octadecane, 2-methyl- octacosane, 1-iodo-, nonacosane, and eicosyl isopropyl ether. Using an egg albumin denaturation inhibition assay, the anti-inflammatory activities of E. prostrata alone and in combination with diclofenac were investigated, and they showed 93% and 99% denaturation inhibition at 5 mg concentration of E. prostrata in alone and combination with diclofenac, respectively. Heat-induced haemolysis showed 2.5% and 2.4% of haemolysis at 5 mg of E. prostrata alone and in combination with diclofenac, respectively. An MTT assay performed using L929 cells proved that the extract has no cytotoxic effect. The plant extract displayed potential antibacterial activity against Staphylococcus aureus; the growth was inhibited at 1 mg/mL of E. prostrata extract. Thus, based on this evidence, the authors suggest that E. prostrata extract should be studied further for its anti-inflammatory and antibacterial activities and topical application in the treatment of atopic dermatitis.